2023
DOI: 10.3390/pharmaceutics15092247
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid in Rheumatology

Haiko Sprott,
Christian Fleck

Abstract: Hyaluronic acid (HA), also known as hyaluronan, is an anionic glycosaminoglycan widely distributed throughout various tissues of the human body. It stands out from other glycosaminoglycans as it lacks sulfation and can attain considerable size: the average human synovial HA molecule weighs about 7 million Dalton (Da), equivalent to roughly 20,000 disaccharide monomers; although some sources report a lower range of 3–4 million Da. In recent years, HA has garnered significant attention in the field of rheumatolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 154 publications
0
2
0
Order By: Relevance
“…Other studies have suggested that the free radical scavenging nature of hyaluronic acid contributes to protection against UVB and UVA radiation, which supports the role of CD44 as a hyaluronic acid receptor in the epidermis [9,10]. The current popularity of hyaluronic acid as an ingredient in cosmetic products and in injectable aesthetic medical devices, alongside emerging research findings on its cellular effects, has instigated further studies [4,[20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 88%
“…Other studies have suggested that the free radical scavenging nature of hyaluronic acid contributes to protection against UVB and UVA radiation, which supports the role of CD44 as a hyaluronic acid receptor in the epidermis [9,10]. The current popularity of hyaluronic acid as an ingredient in cosmetic products and in injectable aesthetic medical devices, alongside emerging research findings on its cellular effects, has instigated further studies [4,[20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 88%
“…In inflammatory contexts of osteoarthritis (OA) or rheumatoid arthritis (RA), HMWHA is dissipated by reactive oxygen species (ROS), reducing the viscous state and compromising its lubricating and shock absorbing potential [56]. This deterioration leads to impaired joint movement and pain [57]. Additionally, reductions in pain associated with intra-articular HA have been linked to a decreased development of bradykinin, prostaglandin E2, and substance P, along with the direct constraint of nociceptive afferents [58].…”
Section: Hyaluronic Acid Injectionmentioning
confidence: 99%